2000
DOI: 10.1002/bdd.241
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic assessment of an oral enalapril suspension for use in children

Abstract: The angiotensin-converting enzyme (ACE) inhibitor enalapril is commonly used to treat pediatric hypertension. Because some children are unable to swallow tablets or require doses less than the lowest available enalapril tablet, an enalapril suspension was developed. This study examined the relative bioavailability of enalapril suspension (10 mg) (S) compared with 10-mg marketed VASOTEC tablets (T) in 16 healthy adult subjects. The geometric mean ratio (S/T) estimate of urinary recovery of free enalaprilat, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
10
1
Order By: Relevance
“…We excluded reports which deal with the pharmacokinetics of antihypertensive agents [2][3][4][5][6][7][8][9], with the management of hypertensive emergency, neonatal hypertension or heart failure, or with the management of minimal range albuminuria in diabetes mellitus [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], or include fewer than 10 individuals [25][26][27][28][29][30][31][32][33][34][35][36]. Trials examining antihypertensive drugs for periods less than 4 weeks [37][38][39], reports not describing the outcome of interest [40][41][42][43][44][45][46][47][48] or describing the effect of a substance added to another, both with the same mechanism of action …”
Section: Study Selectionmentioning
confidence: 99%
“…We excluded reports which deal with the pharmacokinetics of antihypertensive agents [2][3][4][5][6][7][8][9], with the management of hypertensive emergency, neonatal hypertension or heart failure, or with the management of minimal range albuminuria in diabetes mellitus [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], or include fewer than 10 individuals [25][26][27][28][29][30][31][32][33][34][35][36]. Trials examining antihypertensive drugs for periods less than 4 weeks [37][38][39], reports not describing the outcome of interest [40][41][42][43][44][45][46][47][48] or describing the effect of a substance added to another, both with the same mechanism of action …”
Section: Study Selectionmentioning
confidence: 99%
“…Similar to our study, a recent study on a suspension of enalapril for children used adult volunteers [12]. Ideally, this study should have used children as research subjects, as the pediatric suspension is aimed at them.…”
Section: Discussionmentioning
confidence: 57%
“…Ethically, however, it is very difficult to perform a meaningful bioavailability study in children due to the numerous blood samples needed. They concluded that the slow transfer of drug from the gut to the venous circulation is a physiochemical property of amlodipine, and not a consequence of delayed or slow dissolution from the capsule formulation [12]. Very few studies measured bioavailability in children by repeating intravenous and oral doses and no study has compared bioavailability in children with adults.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 This intrarenal conversion was implemented by inclusion of an additional conversion clearance within the intracellular compartment of the kidneys. Data on urinary excretion of enalapril, enalaprilat, and their combination were used to estimate clearance parameters, 49 with a resulting specific intrarenal conversion clearance of 1.95E+05 L$min 21 $kg 21 organ, and an excretion clearance of 0.36 for intrarenal enalaprilat and 3.45 L$min 21 $kg 21 organ for enalapril.…”
Section: Coupled Enalapril/enalaprilat Modelmentioning
confidence: 99%